Effect of Halamphora coffeaeformis supplementation in rice bran biofloc on the growth and survival of black tiger shrimp (Penaeus monodon) postlarvae - Ahmad, Mohd Ihsanuddin; Nazarudin, Muhammad Farhan; Hasnan, Hazwani Hanim; Baharuddin, Ninie Diana; Latif, Kamil; de Cruz, Clement R.; Karim, Murni; Tan, Hui Teng; Khaw, Yam Sim; Lee, Jeffrey K.C.; Natrah, Ikhsan (Springer Science and Business Media Deutschland GmbH, 2025)
The shrimp aquaculture industry is hindered by disease outbreaks and low survival rates, primarily exacerbated by nutritional deficiencies and environmental stressors. This study examined the effects of Halamphora coffeaeformis-supplemented rice bran biofloc on the growth, nutritional composition, and disease resistance of black tiger shrimp (Penaeus monodon) postlarvae (PL). The H. coffeaeformis was added into biofloc at 1 × 104 cells mL−1 (BFR4) And 1× 105 cells mL−1 (BFR5) for eight weeks and compared with a biofloc-only system as control. Shrimp in BFR5 exhibited improved overall growth (p = 0.03) with higher final weight (347.54 ± 74.72 mg) and daily weight gain (5.42 ± 1.19 mg day⁻1) compared to other treatments. The shrimp also had the highest lipid content (2.45 ± 0.15% dry weight; p = 0.03) and enriched fatty acid profile, with elevated eicosapentaenoic acid (3.46 ± 1.25% of total fatty acids) and docosahexaenoic acid (0.65 ± 0.37% of total fatty acids) compared to other treatments. After exposure to Vibrio parahaemolyticus, shrimp in BFR4 and BFR5 exhibited significantly higher survival rates (40.74 ± 6.05% And 39.26 ± 2.20%, respectively; p = 0.04) compared to the control (24.93 ± 4.95%) with histological analysis revealing reduced vacuolation and hepatopancreatic necrosis. These findings highlight the potential of H. coffeaeformis-enriched biofloc to improve shrimp growth, nutritional quality, and disease resistance, thereby supporting sustainable aquaculture practices.